Pengaruh Motivasi, Budaya Organisasi, Lingkungan Kerja Terhadap Kinerja Karyawan - Permana, I Putu Feby; Kawiana, I Gede Putu; Putri Agustina, Made Dian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The existence of high employee performance, especially in banking companies, is very influential in the continuity of the bank. The purpose of this research is to determine the influence of motivation, organizational culture and work environment on employee performance at Bank BPD Bali, Tabanan Branch. This research was conducted at Bank BPD Bali Tabanan Branch with a population of 52 people and the same number of samples, where the sample determination method used saturated samples. The results of this research are that motivation partially has a positive and significant effect on employee performance, organizational culture partially has a positive and significant effect on employee performance, the work environment partially has a positive and significant effect on employee performance, motivation, organizational culture and work environment. simultaneously has a positive and significant effect on employee performance. The suggestions in this research are that Bank BPD Bali Tabanan Branch can provide salaries as compensation for work results on time, in appropriate amounts and can provide bonuses for employees who are able to meet targets, hold outings or gatherings where activities outside the company foster a sense of kinship between colleagues. work and provide job training for employees.